Estudos de QSAR 2D e QSAR 3D para um conjunto de antagonistas de receptores de adenosina 2b, potencialmente úteis no tratamento da anemia falciforme - Paz, Odailson Santos (2012)
The adenosine receptors are involved in many physiological and pathological processes, hence they have been considered as potential targets for the development of drugs against various diseases. The main challenge to achieve this goal is the selective inhibition of one receptor subtype over the others. This topic is particularly crucial for antagonists adenosine A2b receptor (AdoRA2B) which have been identified as promising compounds for the treatment of sickle cell disease, a hemoglobinopathy that is a consequence of a mutation (GLU-VAL) in the beta chain of hemoglobin and affects mainly black people. In order to contribute to the development of drugs against sickle cell disease this project aims to investigate the chemical and structural properties of AdoRA2B that are important for their biological activity. The strategy employed to achieve this goal is based on the quantitative structure activity relationship study (QSAR). Thus 2D-QSAR models have been developed with molecular holograms as descriptors, for a set of 195 deazaxanthine derivatives whose potency ranges from 1.55 nM to 2.19 µM. In order to further investigate the steric and electronic properties that are responsible for the biological activity of these compounds, comparative molecular field (CoMFA), a 3D-QSAR approach, was also carried out. 2D-QSAR and 3D-QSAR models have good statistical quality (HQSAR - r2 = 0.85, q2LOO = 0.77; CoMFA - r2 = 0.86, q2 = 0.70) and predictive ability (r2pred1= 0.78, r2pred2 = 0.78 and r2pred1 = 0.70, r2pred2 = 0.70, respectively). Analysis of contour and contribution maps reveal important features for the affinity of 9-deazaxanthine derivatives, such as the adverse effect of methoxy substituent in the 8-phenyl ring on the activity, whereas bulky substituent near the oxocetamide positively contribute to the affinity of the studied compounds. The association of these results may be useful in design of novel more potent and selective antagonists.